Exploring competitive intelligence in Romania: understanding corporate views and approaches - Raluca LUȚAI; Adina MIHĂESCU (Bulletin of "Carol I" National Defense University)
The awareness and application of Competitive Intelligence (CI) in Romania are significantly less developed than in international markets. This disparity is evident in the limited understanding of CI methodologies and the insufficient allocation of resources dedicated to fostering a CI-oriented culture within Romanian enterprises. Furthermore, the perspectives of market participants on the importance and use of CI have not been thoroughly examined, highlighting a considerable gap in systematic research on this topic. This study aims to address this gap in the existing literature by exploring the perceptions of Romanian firms regarding CI-related activities. Employing a qualitative methodology, the research seeks to assess how organizations recognize the benefits of CI, the extent to which these practices are integrated into their decisionmaking frameworks, and the obstacles that hinder their implementation. By doing so, this study enhances the understanding of CI within the Romanian context and establishes a foundational framework for promoting and advancing CI practices in the local economic landscape.